2001
DOI: 10.1016/s0002-9440(10)61695-1
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability and High Content of Activated Cytotoxic Lymphocytes Identify Colon Cancer Patients with a Favorable Prognosis

Abstract: Colorectal cancers with high-frequency microsatellite instability show peculiar clinicopathological features and a favorable clinical outcome. We investigated whether the improved prognosis for these cancers is related to the content of activated cytotoxic intraepithelial T lymphocytes. Microsatellite instability and the amount of activated cytotoxic lymphocytes were analyzed according to clinicopathological features, survival, and disease recurrence in 109 right-sided colon carcinomas from 245 consecutive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
197
2
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(222 citation statements)
references
References 23 publications
(26 reference statements)
20
197
2
3
Order By: Relevance
“…Furthermore, several studies have found that the degree of lymphocyte infiltration correlates with a better patient survival (Jass, 1986;di Giorgio et al, 1992;Ropponen et al, 1997;Naito et al, 1998). A recent study found that patients with MSI-H tumours with a high content of activated intra-tumour cytotoxic lymphocytes had better prognosis (Guidoboni et al, 2001). This finding supports the presence of an anti-tumour immune response in the MSI-H tumours, which probably explains the better prognosis in these patients.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, several studies have found that the degree of lymphocyte infiltration correlates with a better patient survival (Jass, 1986;di Giorgio et al, 1992;Ropponen et al, 1997;Naito et al, 1998). A recent study found that patients with MSI-H tumours with a high content of activated intra-tumour cytotoxic lymphocytes had better prognosis (Guidoboni et al, 2001). This finding supports the presence of an anti-tumour immune response in the MSI-H tumours, which probably explains the better prognosis in these patients.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, two studies have identified significantly more cytotoxic lymphocytes (CD3, CD8 and TIA-1) and a higher rate of cells undergoing apoptosis in MSI-H colorectal carcinomas than in MSI-L and MSS (Dolcetti et al, 1999;Michael-Robinson et al, 2001). Furthermore, patients with MSI-H tumours and a high content of activated cytotoxic lymphocytes showed improved overall survival (Guidoboni et al, 2001). Some studies have reported improved survival among colorectal cancer patients with microsatellite unstable tumours (Lothe et al, 1993;Thibodeau et al, 1993;Bubb et al, 1996;Lukish et al, 1998;Halling et al, 1999;Johannsdottir et al, 1999;Massa et al, 1999;Elsaleh et al, 2000;Gryfe et al, 2000;Hemminki et al, 2000;Wright et al, 2000;Ward et al, 2001;Watanabe et al, 2001), while others have not (Messerini et al, 1997;Senba et al, 1998;Feeley et al, 1999;Salahshor et al, 1999;Curran et al, 2000).…”
mentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33] As in this study, MSI tumors have previously been reported to have a higher degree of T-cell infiltration than MSS tumors. [35][36][37] Yet the potential confounding effect of MSI screening status on the prognostic importance of T-cell infiltration has been considered in only a minority of reports, of which most, 32,36,[39][40][41]46,53,54 but not all, 30,55 found that the better prognosis associated with dense T-cell infiltration was independent of MSI screening status. In this study, a better prognosis was seen in patients with MSS tumors densely infiltrated by T cells compared with poorly or intermediately infiltrated MSI tumors, whereas MSI screening status was not significantly related to prognosis in subgroups of highly and poorly infiltrated tumors separately.…”
Section: Discussionmentioning
confidence: 99%
“…34 CIMP-high and MSI tumors are frequently infiltrated by a large number of T cells. 4,[35][36][37][38] However, few large studies of tumor infiltrating T cells and colorectal cancer patient survival have taken into account the potentially confounding effect of MSI screening status, 30,32,[39][40][41][42] and only one other research group has considered CIMP. 32,42 Furthermore, T-cell infiltration can be assessed in various locations within the tumor, such as the tumor front, tumor center, and the intraepithelial compartment, but few studies have evaluated these separately.…”
mentioning
confidence: 99%
“…Consequently it has been suggested that these lymphocytes may actually represent an immune response that contributes to improved survival of MSI-H CRC and subsequent work has confirmed a possible link ( Table 2). Guidoboni et al [72] showed a significantly higher prevalence of activated CD8 + IEL in MSI+ versus MSI-CRC, suggesting that the occurrence of a local cytotoxic immune response may be the major determinant of the good clinical course of these MSI+ CRC patients. Dolcetti et al [71] and Michael-Robinson et al [73] demonstrated that the increased frequency of TILs associated with MSI-H cancers are only weakly or moderately correlated with tumor apoptosis.…”
Section: Role In Prognosismentioning
confidence: 99%